9th International Conference on music perception and cognition, 6th Triennial conference of the European socienty for the cognitive scienes of music. Abstracts - Adessi, Anna Rita; Baroni, Mario; Catarina, Roberto; Costa, Marco (Bologna Bononia University Press, 2006)
The focus of the 9th ICMPC is interdisciplinary discussion and dissemination of new, unpublished research relating to the field of music perception, cognition and education.